Consumer exposure to food and beverage advertising out of home: An exploratory case study in Jamaica. (23rd January 2020) - Nelson, Michelle R.; Ahn, Regina Jihea; Ferguson, Gail M.; Anderson, Arianne
Abstract: Consumers are inundated with messages about food and beverages in their daily lives. Research has shown that television advertising contains frequent low‐nutrient food and beverage messages which are thought to influence consumers' food consumption. Yet, consumption decisions are often made out of the home. We systematically capture and describe food and beverage consumer communications at or near the point of purchase through observation of messages in food environments (Study 1: retail, restaurant) and content analysis of out‐of‐home advertising (Study 2: billboards). To do so, we focus on Jamaica, a ‐middle‐income country that is experiencing a nutrition transition from a traditional to a Westernized diet featuring refined carbohydrates, sugars, fats, sodium and processed foods. Globalization of food and beverage brands is one of the contributory factors to dietary changes and the prevalence of obese and overweight Jamaican consumers is a serious health issue. However, there is no research on advertising in Jamaica to help inform the understanding of its influence on consumers' health. Therefore, we gauge the prevalence and persuasion techniques across two forms of local and global food and beverage advertising that are rarely investigated (retail/restaurant, outdoor). Findings reveal that fast food and sugary beverages, mostly of U.S. origin, were predominantly promoted. Observations in grocery stores and fast‐food restaurants included point‐of‐purchase displays, posters and sales promotion tactics, most typically for low‐nutrient foods. Content analysis results revealed that one in four outdoor advertisements was for a food or beverage. The most frequently advertised foods were energy‐dense processed foods, sodas and fast‐food restaurants. These advertisements typically featured the brand name and a visual. As a whole, this study presents a unique descriptive snapshot which suggests that consumers in Kingston, Jamaica are exposed to multiple messages for low‐nutrient foods in their everyday lives and near the point of purchase.